Risk Factors for Undernutrition among Children in South Central Somalia - Zikusooka, Monica; Tawfik, Hebatullah; Robare, Joseph (International Journal of Child Health and Nutrition, 2022)
Objectives: Undernutrition is a global public health challenge, especially in countries that experience extreme climate conditions and armed conflict. In Somalia, undernutrition is chronic, often graded for emergency response. The purpose of this study was to provide evidence on immediate, proximate, and distal risk factors for undernutrition in the most affected region of Somalia. Setting: Data for the study was from cross-sectional nutritional surveys implemented by the Somalia Food Security and Nutrition Analysis Unit. Sampling for the surveys followed a multistage cluster sampling methodology where in the first stage, 30 clusters were randomly assigned to villages, and then 30 households were randomly selected from each cluster. Generalized Estimation Equations were used to determine risk factors for undernutrition. Data analysis followed survey analysis procedures. Participants: 60,856 children aged 6-59 months from cross-sectional nutritional surveys implemented in South-Central Somalia from 2007 to 2012. Results: When factors at the individual, household, and society level were considered simultaneously, diarrhea diseases and geographical region were the main risk factors for underweight, child gender, meal frequency, and livelihood zone were risk factors for stunting, while diarrhea and livelihood zone were the risk factors for wasting. Geographical region and livelihood system were significant factors for undernutrition. Conclusions: Interventions to address undernutrition in Somalia should be tailored to the region and livelihood zone while prioritizing innovative climate-smart food production and addressing childhood illnesses. The study findings provide evidence to inform nutrition policy and programs that could eliminate nutrition disparities and the burden of childhood undernutrition in Somalia and other countries with similar contexts.